2019
DOI: 10.4067/s0716-10182019000400428
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo socio-demográficos del síndrome cardiopulmonar por hantavirus

Abstract: Sociodemographic risk factors of hantavirus cardiopulmonary syndrome Background: Hantavirus cardiopulmonary syndrome (HCPS) is caused by new world hantaviruses, among which Andes hantavirus (ANDV) is endemic to Chile and Southern Argentina. The disease caused by ANDV produces plasma leakage leading to enhanced vascular permeability and has a high case fatality rate (35%), mainly due to respiratory failure, pulmonary edema and myocardial dysfunction, hypoperfusion and shock. Host sociodemographic and genetic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The objective is to advance this product through preclinical testing and ultimately carry out a Phase 1 clinical study, paving the path for potential therapeutic applications. Table 3 (Vilcek, 1991;Murphy et al, 2000Murphy et al, , 2001Sundstrom et al, 2001;Glass et al, 2003;Maes et al, 2004;Chung et al, 2008Chung et al, , 2013Hall et al, 2008;Antonen et al, 2013;Ogg et al, 2013;Safronetz et al, 2013;Vial et al, 2013Vial et al, , 2015Laine et al, 2015;Barriga et al, 2016;Bird et al, 2016;Garrido et al, 2018;Brocato and Hooper, 2019).…”
Section: Polyclonal Antibodiesmentioning
confidence: 99%
“…The objective is to advance this product through preclinical testing and ultimately carry out a Phase 1 clinical study, paving the path for potential therapeutic applications. Table 3 (Vilcek, 1991;Murphy et al, 2000Murphy et al, , 2001Sundstrom et al, 2001;Glass et al, 2003;Maes et al, 2004;Chung et al, 2008Chung et al, , 2013Hall et al, 2008;Antonen et al, 2013;Ogg et al, 2013;Safronetz et al, 2013;Vial et al, 2013Vial et al, , 2015Laine et al, 2015;Barriga et al, 2016;Bird et al, 2016;Garrido et al, 2018;Brocato and Hooper, 2019).…”
Section: Polyclonal Antibodiesmentioning
confidence: 99%
“…The incidence according to the place of infection has a homogeneous distribution trend between home, work, and outings in the region. While at the national level, infection in the home or surroundings is present in more than 50% of cases (Vial et al, 2019). The distribution of cases in the Ñuble region occurs mainly in communes with high rurality, especially the foothills of Ñuble, and the communes with the highest number of visitors in the summer.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ñuble region the risk factors for acquiring the infection, are mostly being a resident in the rural sector, and a farmer or forestry worker. At the national level, the infection risk rises for people living in the rural sector (Vial et al, 2019). The incidence according to the place of infection has a homogeneous distribution trend between home, work, and outings in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Mertz et al [22][23][24] conducted trials evaluating the antiviral and anti-inflammatory activity of intravenous ribavirin, methylprednisolone, and immune plasma obtained by plasmapheresis and their role in the supportive care of HCPS patients, as well as retrospectively investigating a case series treated with extracorporeal membrane oxygenation (ECMO). They stated that ECMO can reduce the risk of death in severe cases of HCPS, but cited the risk of morbidity and mortality and its relative inaccessibility as drawbacks of this treatment [23] . including 60 patients indicated that parenterally administered methylprednisolone was not effective for treatment.…”
Section: Treatment Antiviral Drugsmentioning
confidence: 99%